A perovskite light absorbing layer and a preparation method thereof, a perovskite solar cell containing the same and a preparation method thereof

The fixation of halogen ions through the hydrogen bond frame assembly solves the problem of halogen ions migration in perovskite solar cells and improves the stability and performance of the device.

CN118804608BActive Publication Date: 2024-12-20CHINT NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411274064.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-20
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The migration of halogen ions in perovskite solar cells leads to instability of the device and affects long-term operating performance. It is difficult for the existing technology to effectively solve this problem.

Method used

The hydrogen bond frame assembly chemical method is used to form a hydrogen bond frame assembly through tetra-(4-aminobenzene)ethylene halide and halogen anions to fix the halogen ions and reduce their migration.

Benefits of technology

It significantly improves the stability and carrier transmission efficiency of perovskite batteries, extends the service life of the device and reduces the generation of defect states.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118804608B_ABST
    Figure CN118804608B_ABST
Patent Text Reader

Abstract

The present invention provides a perovskite light-absorbing layer and a preparation method thereof, a perovskite solar cell containing the same and a preparation method thereof, wherein the perovskite light-absorbing layer is formed by a composite of a perovskite material and a halogen complex; the halogen complex comprises a halogen anion ligand, and the halogen anion ligand is combined with at least two halogen anions. The present invention introduces the halogen complex into the perovskite film, and the halogen complex can form a halogen hydrogen bond framework assembly, which can more firmly fix the halogen ions and limit the ion migration in the perovskite battery. The perovskite / halogen complex composite film prepared in this way is used in the perovskite battery, which can reduce the halogen ion migration of the perovskite from the source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells and relates to a perovskite light-absorbing layer and a preparation method thereof, a perovskite solar cell containing the same and a preparation method thereof. Background Art

[0002] Among many clean and renewable energy sources, solar energy has been widely favored due to its large reserves, wide distribution, cleanliness and reliability. Solar cells directly convert light energy into electrical energy, which is one of the most effective means of utilizing solar energy. The life of the battery device and the photoelectric conversion efficiency are two key factors. Among the third-generation photovoltaic semiconductor materials, perovskite materials have attracted widespread attention due to their excellent photoelectric properties and low-cost preparation process. The corresponding solar cell photoelectric conversion efficiency has rapidly increased from 3.8% in 2009 to 26.1% in recent years. At the same time, the band gap of perovskite materials is adjustable. Wide-bandgap mixed halogen perovskites can be used as top cells in stacked cells because of their ideal band gap, thereby improving the utilization of the solar spectrum.

[0003] However, whether it is a single-junction perovskite cell or a perovskite top cell in a stacked cell, due to the particle characteristics of the perovskite material, under the conditions of light and electric field, the perovskite film is prone to ion migration, and heating, light and electric field effects will significantly aggravate the occurrence of ion migration, resulting in unstable performance of the device. In addition, as a wide-bandgap mixed halogen perovskite, it will also cause phase separation due to halogen ion migration, further leading to the degradation of device performance, which is not conducive to the long-term operation stability of the device and seriously hinders the future commercialization of perovskite cells. Scientific research shows that the fundamental reason for the migration of perovskite ions is the low activation energy of ion migration of halogen ions, especially halogen ions located at the grain boundaries. This is because the halogen ions at the grain boundaries only bind to half of the cations, so the energy required for the migration of halogen ions at the grain boundaries is only about half of that inside the crystal. The existing technology mainly inhibits ion migration by passivating surface defects, but the additives are usually combined with Pb dangling bonds, and do not fundamentally solve the problem of halogen ion migration.

[0004] Therefore, in the art, it is desired to develop a perovskite solar cell that can fundamentally solve the problem of halogen ion migration. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a perovskite light-absorbing layer and a preparation method thereof, a perovskite solar cell comprising the same and a preparation method thereof, and specifically to provide a perovskite / tetrakis-(4-aminophenyl)ethylene halide solar cell based on hydrogen bond framework assembly chemistry and a preparation method thereof. The perovskite solar cell provided by the present invention can fundamentally solve the problem of halogen ion migration.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a perovskite light absorbing layer, wherein the perovskite light absorbing layer is formed by combining a perovskite material and a halogen complex;

[0008] The halogen complex includes a halogen anion ligand that is bound to at least two (eg, three, four, etc.) halogen anions.

[0009] Preferably, the halide anion ligand binds to at least three halide anions.

[0010] Preferably, the halogen anion ligand forms a cubic structure with the halogen anion.

[0011] Preferably, the halogen complex comprises tetrakis-(4-aminophenyl)ethylene halide, wherein the benzene rings in the tetrakis-(4-aminophenyl)ethylene halide are not located in the same plane.

[0012] Preferably, the molecular structure of the tetrakis-(4-aminophenyl)ethylene halide is shown in the following formula I:

[0013]

[0014] Formula I

[0015] The benzene rings in formula I are not located in the same plane, and the anion X - Selected from Cl - Br - or I - Any one or a combination of at least two of - (This is because the halogen in the current mainstream perovskite materials is mainly I - Mainly).

[0016] Due to the steric effect, the four benzenes in the actual configuration of the molecule are not in the same plane.

[0017] In the present invention, tetrakis-(4-aminophenyl)ethylene halide forms a hydrogen bond framework assembly with the halogen ions on the surface of the perovskite, wherein tetrakis-(4-aminophenyl)ethylene acts as a hydrogen bond donor and the halogen anion (Cl - ,Br - , I - ) as a hydrogen bond acceptor. The charge-assisted hydrogen bonding between the protonated tetra-(4-aminophenyl)ethylene and the halogen anion is achieved through the positively charged ammonium radical and the negatively charged Cl - Br - ,I - Strong hydrogen bonding was formed, and a structurally stable halogen hydrogen bonding framework assembly was successfully assembled.

[0018] By utilizing the property of tetra-(4-aminophenyl)ethylene ligands to combine with halogen anions through hydrogen bonding, hydrogen bonding interactions can be formed with halogen ions at the perovskite grain boundaries. In addition, unlike other additives that can form hydrogen bonds with halogens, eight tetra-(4-aminophenyl)ethylene ligands can form a structurally stable halogen hydrogen bonding framework assembly with eight halogen anions, in which the halogens at the eight vertices of the halogen hydrogen bonding framework assembly are shared with the halogens at the perovskite grain boundaries, thereby fixing the halogens at the grain boundaries that are most likely to undergo ion migration. The action mechanism of the halogen hydrogen bonding framework assembly in the perovskite light-absorbing layer is shown in the figure below. Figure 1 As shown, on the octahedron, the gray negatively charged represents the halogen anion, the black positively charged represents the tetra-(4-aminophenyl)ethylene ligand, and the two sides of the octahedron represent the perovskite light-absorbing layer. In the present invention, the tetra-(4-aminophenyl)ethylene ligand refers to the protonated tetra-(4-aminophenyl)ethylene ion with four positive charges.

[0019] The present invention adds the same amount of aminobenzene halide to the perovskite for comparative experiments. The aminobenzene halide is a substructure of a tetra-(4-aminophenyl)ethylene ligand and a halogen to form a hydrogen bond. The difference is that the aminobenzene halide is a separate small molecule, while the tetra-(4-aminophenyl)ethylene halide is four aminobenzene halides covalently connected to the structure of ethylene, wherein the double bond is rigid. The comparative experiment shows that the tetra-(4-aminophenyl)ethylene halide can better passivate surface defects, inhibit ion migration, thereby improving carrier transfer efficiency, and most importantly, significantly improve the stability of the perovskite battery. This is because there is an electrostatic interaction between aminobenzene and halogen ions, mainly one cation corresponds to one anion, and in the halogen hydrogen bond framework assembly formed based on the unique rigid structure of tetrakis-(4-aminophenyl)ethylene halide, each halogen is bound to three tetrakis-(4-aminophenyl)ethylene ligands through electrostatic interaction, and each tetrakis-(4-aminophenyl)ethylene ligand is bound to two halogen ions, resulting in a stronger interaction between the ligands and the halogen ions, so as to more firmly lock the halogen ions in the perovskite, reduce the loss of ions caused by the perovskite preparation process, and thus inhibit the migration of halogen ions from the source, thereby reducing the generation of defect states in the perovskite film and increasing the stability of the perovskite film.

[0020] The present invention does not specifically limit the preparation method of the tetrakis-(4-aminophenyl)ethylene halide. For example, taking tetrakis-(4-aminophenyl)ethylene iodide as an example, the preparation method thereof comprises the following steps:

[0021] Dissolve 22 g of tetrakis-(4-aminophenyl)ethylene (CAS: 78525-34-5, which can be purchased directly) in 2 L of methanol, then add 30 mL of HI solution (57 wt%), and stir at room temperature for more than 6 hours. Then, remove the solvent by rotary evaporation at 40°C to obtain a solid, which is tetrakis-(4-aminophenyl)ethylene iodide.

[0022] For other halides, replace the HI solution with equimolar HCl solution and HBr solution.

[0023] Preferably, the structure of the perovskite material is ABX3, wherein A is FA + (formamidinium ion), MA + (methylamine ion) or Cs + Any one or a combination of at least two of the following: B is Pb 2+ and / or Sn 2+ ; X is Cl - Br - or I - Any one or a combination of at least two of the following.

[0024] Preferably, the thickness of the perovskite light absorbing layer is 200-800 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, etc.

[0025] In a second aspect, the present invention provides a method for preparing a perovskite light absorbing layer as described in the first aspect, wherein the perovskite light absorbing layer is prepared by a solution method, and an anti-solvent is added during the film formation process of the perovskite precursor solution.

[0026] Preferably, in the perovskite precursor solution, Pb 2+ and / or Sn 2+ The concentration is 0.5-2 mol / L, for example, 0.5 mol / mL, 0.8 mol / mL, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, etc., preferably 1-1.7 mol / L.

[0027] Preferably, in the perovskite precursor solution, the concentration of the halogen complex is 0.5-20 mg / mL, for example, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, etc., preferably 2-10 mg / mL.

[0028] Preferably, the anti-solvent comprises toluene and / or chlorobenzene.

[0029] Preferably, the solution method includes any one of a spin coating method, a blade coating method or a slit coating method.

[0030] Preferably, when the spin coating method is adopted, the spin coating rotation speed is 3000-4000 rpm, for example, 3000 rpm, 3100 rpm, 3200 rpm, 3300 rpm, 3400 rpm, 3500 rpm, 3600 rpm, 3700 rpm, 3800 rpm, 3900 rpm, 4000 rpm, etc., and the spin coating time is 20-40 s, for example, 20 s, 22 s, 24 s, 26 s, 28 s, 30 s, 32 s, 34 s, 36 s, 38s, 40 s, etc.

[0031] In a third aspect, the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the perovskite light absorbing layer as described in the first aspect.

[0032] Preferably, the perovskite solar cell comprises a single-junction perovskite solar cell or a tandem perovskite solar cell.

[0033] Preferably, the single-junction perovskite solar cell comprises, from bottom to top, a transparent electrode, a first transmission layer, a perovskite light absorption layer, a second transmission layer and a metal electrode.

[0034] Preferably, the stacked perovskite solar cell is formed by using a crystalline silicon cell as a substrate and connecting the single-junction perovskite solar cell in series via a tunneling layer.

[0035] Preferably, the first transport layer is an electron transport layer, and the second transport layer is a hole transport layer (in this case, the perovskite solar cell structure is a formal structure); or, the first transport layer is a hole transport layer, and the second transport layer is an electron transport layer (in this case, the perovskite solar cell structure is a trans structure). The novel hydrogen bond framework assembly chemical strategy for modifying the perovskite light-absorbing layer provided by the present invention can be applied to the above two commonly used battery structures.

[0036] Preferably, the crystalline silicon cell comprises a TOPCon cell or a HJT cell. It should be noted that the present invention does not impose any specific limitation on the structure of the crystalline silicon cell.

[0037] In a fourth aspect, the present invention provides a method for preparing a perovskite solar cell as described in the third aspect, wherein the method for preparing a single-junction perovskite solar cell comprises the following steps:

[0038] (1) depositing a first transport layer on the transparent electrode;

[0039] (2) mixing a perovskite precursor material, a halogen complex and a solvent to obtain a perovskite precursor solution, coating the perovskite precursor solution on the first transport layer, adding an anti-solvent to assist film formation during the film formation process, and heating to obtain a perovskite light absorbing layer;

[0040] (3) depositing a second transmission layer on the perovskite light absorbing layer, and finally evaporating a metal electrode on the second transmission layer to obtain the single-junction perovskite solar cell.

[0041] The method for preparing the stacked perovskite solar cell comprises the following steps:

[0042] The single-junction perovskite solar cell and the crystalline silicon cell are connected in series via a tunneling layer to obtain the stacked perovskite solar cell.

[0043] Preferably, the perovskite precursor material in step (2) includes but is not limited to any one of CsI, CsBr, MAI, FAI, PbI2, MACl, FABr, or a combination of at least two thereof.

[0044] Preferably, the solvent in step (2) comprises N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO).

[0045] Preferably, in the perovskite precursor solution of step (2), Pb 2+ and / or Sn 2+The concentration is 0.5-2 mol / L, for example, 0.5 mol / mL, 0.8 mol / mL, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, etc., preferably 1-1.7 mol / L.

[0046] Preferably, in the perovskite precursor solution of step (2), the concentration of the halogen complex is 0.5-20 mg / mL, such as 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, etc. If the concentration of the halogen complex is less than 0.5 mg / mL, the concentration of the additive is insufficient to fully passivate the interface defects; if the concentration of the halogen complex is greater than 20 mg / mL, too much additive will accumulate at the grain boundaries, resulting in reduced transmission.

[0047] Preferably, the anti-solvent in step (2) comprises toluene and / or chlorobenzene.

[0048] Preferably, the coating in step (2) comprises any one of spin coating, blade coating or slit coating.

[0049] Preferably, when the coating is spin coating, the spin coating rotation speed is 3000-4000 rpm, for example, 3000 rpm, 3100 rpm, 3200 rpm, 3300 rpm, 3400 rpm, 3500 rpm, 3600 rpm, 3700 rpm, 3800 rpm, 3900 rpm, 4000 rpm, etc., and the spin coating time is 20-40 s, for example, 20 s, 22 s, 24 s, 26 s, 28 s, 30 s, 32 s, 34 s, 36s, 38 s, 40 s, etc.

[0050] Preferably, the heating temperature in step (2) is 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc., and the heating time is 20-40 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The present invention introduces a halogen complex into a perovskite film. The halogen complex can form a halogen hydrogen bond framework assembly, which can more firmly fix the halogen ions and limit the ion migration in the perovskite battery. The perovskite / halogen complex composite film prepared in this way is used in the perovskite battery, which can reduce the halogen ion migration of the perovskite from the source.

[0053] Compared with single-molecule aminobenzene halides, the present invention uses halogen complexes as additives, which can better inhibit the migration of halogen ions, significantly inhibit the occurrence of ion migration in perovskite, greatly reduce the generation of defect states in perovskite films, and improve the carrier transport characteristics of perovskite films and the stability of battery devices. The present invention truly realizes the inhibition of ion migration inside perovskite materials and obtains efficient and stable perovskite battery devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 Diagram of the action mechanism of halogen hydrogen bond framework assembly in the perovskite light-absorbing layer. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Unless otherwise specified, all chemical reagents used in the present invention are commercially available chemical reagents.

[0057] Example 1

[0058] In this embodiment, a perovskite solar cell is provided, specifically a wide bandgap mixed halogen perovskite cell, and a preparation method thereof comprises the following steps:

[0059] (1) Cleaning the ITO conductive glass substrate: ultrasonically clean the ITO conductive glass substrate with deionized water, anhydrous ethanol, and acetone, respectively, dry it in an oven at 150°C for 2 hours to obtain a clean and dry conductive glass substrate, and then treat it with ozone under a UV lamp for 20 minutes.

[0060] (2) Preparation of hole transport layer: Poly (bis (4-phenyl) (2,4,6-trimethylphenyl) amine (PTAA)) was deposited on ITO conductive glass by solution method as the hole transport layer. The specific process is as follows: 100 μL of 2 mg / mL PTAA chlorobenzene solution was taken and placed on ITO conductive glass (2*2 cm 2), the rotation speed of the coating machine is 5000 rpm, the spin coating time is 30 s, and the spin-coated ITO conductive substrate is placed on a heating table for annealing, the annealing temperature is 100° C., and the annealing time is 10 min.

[0061] (3) Preparation of perovskite light absorbing layer: A perovskite layer was prepared on the hole transport layer. The specific process was as follows: 1.5 mmol PbI2, 1.4 mmol FAI, and 0.7 mmol MACl were dissolved in 0.8 mL DMF and 0.2 mL DMSO, 1 mmol MABr and 1 mmol PbBr2 were dissolved in 0.8 mL DMF and 0.2 mL DMSO, and 1.5 mmol CsI was dissolved in 1 mL DMSO. The three solutions were mixed in a volume ratio of 72:28:5, and then tetrakis-(4-aminophenyl)ethylene iodide was added at a concentration of 3 mg / mL to obtain a perovskite precursor solution. 200 μL of the perovskite precursor solution was added to the substrate coated with the hole transport layer, and the substrate was spin-coated at a speed of 3500 rpm for 30 s. After 20 s of spin-coating, 300 μL of chlorobenzene was quickly added as an anti-solvent. The spin-coated substrate was placed on a heating platform for annealing at a temperature of 100° C. for 30 min.

[0062] (4) Preparation of electron transport layer: An electron transport layer is prepared on the perovskite light absorbing layer. The specific process is as follows: 25 nm of (C60) and 8 nm of 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP) are deposited as the electron transport layer by vacuum evaporation. The evaporation rate is controlled at about 0.1 nm / s.

[0063] (5) Silver was deposited on the electron transport layer by vacuum evaporation with a thickness of 100 nm and the evaporation rate was controlled at about 0.2 nm / s.

[0064] Example 2

[0065] The only difference between this example and Example 1 is that 3 mg / mL of tetrakis-(4-aminophenyl)ethylene iodide is replaced by 0.6 mg / mL of tetrakis-(4-aminophenyl)ethylene bromide and 2.4 mg / mL of tetrakis-(4-aminophenyl)ethylene iodide.

[0066] The I:Br ratio in the perovskite in Example 1 is about 3-4. Therefore, the ratio of tetrakis-(4-aminophenyl)ethylene iodide to tetrakis-(4-aminophenyl)ethylene bromide in the example, that is, the I:Br ratio in the additive is 4, which is close to the ratio of wide bandgap perovskite.

[0067] Comparative Example 1

[0068] The only difference between this comparative example and Example 1 is that 3 mg / mL of tetrakis-(4-aminophenyl)ethylene bromide in step (3) is replaced by 3 mg / mL of aminobenzene bromide.

[0069] Comparative Example 2

[0070] The only difference between this comparative example and Example 1 is that tetrakis-(4-aminophenyl)ethylene bromide is not added in step (3).

[0071] The perovskite solar cells provided in Example 1 and Comparative Examples 1-2 were tested for performance. The current and voltage tests were based on a Keithley 2400 source meter and a G2V Pico solar simulator. The spectral intensity of the solar simulator met AM1.5G. The bias voltage was scanned from -0.1 V to 1 V and then from 1 V to -0.1 V at a scan rate of 0.2 V·s -1 .

[0072] Stability test: Test the initial conversion efficiency of the solar cell, then operate it continuously for 500 hours under AM1.5G light in a nitrogen atmosphere, and test the conversion efficiency again to obtain the efficiency decay rate of the solar cell after 500 hours of continuous operation (i.e., the percentage of the initial efficiency decay).

[0073] The performance test results are shown in Table 1.

[0074] Table 1

[0075]

[0076] As can be seen from Table 1, the stability of the perovskite solar cell obtained by the present invention is high, and the efficiency decay rate is less than 2% after continuous operation for 500 hours. By the comparison of Example 1, Example 2 and Comparative Example 1, it can be seen that compared with aminobenzene halides, the tetra-(4-aminobenzene)ethylene ligand provided by the present invention can be more firmly fixed by the novel halogen hydrogen bond framework assembly formed, so the device efficiency and stability obtained are better. By the comparison of Example 2 and Comparative Example 2, it can be seen that the tetra-(4-aminobenzene)ethylene ligand provided by the present invention can significantly improve the stability of the wide band gap perovskite battery. As can be seen from Examples 1 and 2, tetra-(4-aminobenzene)ethylene iodide and tetra-(4-aminobenzene)ethylene bromide are added at the same time, and the ratio is basically the same as that of the wide band gap perovskite, and the device efficiency and stability obtained are better.

[0077] Example 3

[0078] In this embodiment, a perovskite solar cell is provided, specifically an iodine-based perovskite cell, which is used for a single-junction perovskite cell. The preparation method includes the following steps:

[0079] (1) Cleaning the ITO conductive glass substrate: ultrasonically clean the ITO conductive glass substrate with deionized water, anhydrous ethanol, and acetone, respectively, dry it in an oven at 150°C for 2 hours to obtain a clean and dry conductive glass substrate, and then treat it with ozone under a UV lamp for 20 minutes.

[0080] (2) Preparation of electron transport layer: The specific process is as follows: dilute the commercial SnO2 colloidal aqueous solution with deionized water at a volume ratio of 1:3 and directly coat it on the ITO conductive substrate (2*2 cm 2 ) was dropped with 200 μL of the solution, spin-coated at 2000 rpm for 30 s, and then heated on a hot plate at 150°C for half an hour to obtain a dense SnO2 film, i.e., an electron transport layer.

[0081] (3) Preparation of perovskite light absorbing layer: A perovskite light absorbing layer was prepared on the electron transport layer. The specific process was as follows: 1 mmol PbI2, 0.25 mmol FAI and 0.75 mmol MAI were added to 0.7 mL of DMF and 0.3 mL of DMSO mixed solvent, respectively, and then 5 mg of tetrakis-(4-aminophenyl)ethylene iodide was added. The mixture was stirred under N2 atmosphere until it was completely dissolved to obtain a perovskite precursor solution. The perovskite precursor solution was spin-coated on the electron transport layer at a speed of 4000 rpm on the substrate coated with the electron transport layer. The spin coating time was 30 s. At the 8th s, 300 μL of chlorobenzene antisolvent was quickly dripped on the perovskite film. After the spin coating was completed, a perovskite film was obtained. Then, the film was heated at 150°C for 30 min under N2 atmosphere to obtain a uniform and dense perovskite / tetrakis-(4-aminophenyl)ethylene iodide composite film, that is, a perovskite light absorbing layer was obtained.

[0082] (4) Preparation of hole transport layer: A hole transport layer was prepared on the perovskite light absorbing layer. The specific process was as follows: 70 mg / mL of Spiro-MeOTAD solution was spin-coated on the prepared perovskite light absorbing layer at a spin-coating speed of 3000 rpm for 30 s and then placed in air for 2 h.

[0083] (5) Preparation of metal electrodes: A layer of gold electrode was deposited on the hole transport layer using a vacuum evaporation coating apparatus. The electrode thickness was approximately 100 nm and the deposition rate was 0.1 nm / s.

[0084] Example 4

[0085] The only difference between this example and Example 3 is that 0.5 mg of tetrakis-(4-aminophenyl)ethylene iodide is added in step (3).

[0086] Example 5

[0087] The only difference between this example and Example 3 is that 20 mg of tetrakis-(4-aminophenyl)ethylene iodide is added in step (3).

[0088] Example 6

[0089] The only difference between this example and Example 3 is that 0.3 mg of tetrakis-(4-aminophenyl)ethylene iodide is added in step (3).

[0090] Example 7

[0091] The only difference between this example and Example 3 is that 25 mg of tetrakis-(4-aminophenyl)ethylene iodide is added in step (3).

[0092] Comparative Example 3

[0093] The only difference between this comparative example and Example 3 is that tetrakis-(4-aminophenyl)ethylene iodide is not added in step (3).

[0094] The perovskite solar cells provided in Examples 3-7 and Comparative Example 3 were subjected to performance tests using the same testing methods as in Example 1 above.

[0095] The performance test results are shown in Table 2.

[0096] Table 2

[0097]

[0098] It can be seen from Table 2 that, as the preferred technical solution of the present invention, the perovskite solar cell provided by the present invention has high stability, and the efficiency decay rate is less than 3% after continuous operation for 500 hours.

[0099] Example 8

[0100] In this embodiment, a laminated perovskite solar cell is provided, and a preparation method thereof comprises the following steps:

[0101] (1) On the cleaned and textured 210 mm*210 mm n-type single crystal silicon (C-Si), a layer of amorphous silicon was deposited by plasma enhanced chemical vapor deposition process, with a thickness of 10 nm (ia-Si) and 8 nm (ia-Si), respectively.

[0102] (2) A 15 nm layer of P-type amorphous silicon (Pa-Si) is deposited on the 10 nm ia-Si, and a 10 nm layer of N-type amorphous silicon (Na-Si) is deposited on the 8 nm 404-ia-Si.

[0103] (3) Two layers of ITO with a thickness of 25 nm were prepared on Pa-Si and Na-Si by magnetron sputtering, respectively.

[0104] (4) Several 25*25 mm HJT small batteries are obtained through laser cutting process.

[0105] (5) After edge passivation, a layer of nickel oxide (NiOx) was sputtered on the ITO near the Na-Si side of the HJT small battery by magnetron sputtering as a hole transport layer with a thickness of 15 nm.

[0106] (6) Deposition of Me-4PACz layer on NiOx by vacuum evaporation, the vacuum degree is controlled at 10 -5 Pa, the rate was controlled at 0.2 Å / s, the film thickness was monitored by a film thickness meter, and the thickness was 3 nm. Then the substrate with the Me-4PACz layer was transferred to a closed chamber. A 500 mL beaker containing anhydrous ethanol was placed in advance in the chamber, and the volume of anhydrous ethanol was 200 mL. The beaker was placed on a heating plate at 70°C. The substrate was placed in the closed chamber for 2 minutes and then left to stand in a nitrogen glove box for half an hour.

[0107] (7) A perovskite light absorbing layer is deposited on the Me-4PACz layer. The deposition process is as follows: 2.8 mmol cesium iodide CsI, 11.2 mmol formamidine iodide FAI, 0.07 mmol phenethylammonium iodide, 5.6 mmol lead iodide PbI2, and 8.4 mmol lead bromide PbBr2 are weighed, and then 50 mg of tetrakis-(4-aminophenyl)ethylene iodide is added. 8 mL of N,N'-dimethylformamide DMF and 2 mL of dimethyl sulfoxide DMSO are added to the mixture, and the mixture is stirred thoroughly to completely dissolve. After filtering, a precursor solution is formed. A perovskite film of about 400 nm is prepared as a perovskite light absorbing layer by a solution method.

[0108] (8) About 25 nm of fullerene (C60) and about 8 nm of 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP) were deposited on the perovskite layer by vacuum evaporation as electron transport layers.

[0109] (9) A layer of SnO2 with a thickness of 8 nm was deposited on the electron transport layer by atomic layer deposition to reduce the damage to the substrate caused by the subsequent sputtering process.

[0110] (10) A layer of ITO with a thickness of 40 nm was prepared on the SnO2 layer by magnetron sputtering.

[0111] (11) A metallic silver electrode with a thickness of 100 nm was deposited on the transparent oxide layer by vacuum evaporation.

[0112] (12) A metal silver electrode with a thickness of 500 nm is deposited on the layer close to Pa-Si in the HJT cell by vacuum evaporation.

[0113] Comparative Example 4

[0114] The only difference between this comparative example and Example 8 is that tetrakis-(4-aminophenyl)ethylene iodide is not added in step (7).

[0115] The performance test results are shown in Table 3.

[0116] Table 3

[0117]

[0118] It can be seen from Table 3 that the stacked perovskite solar cell provided by the present invention has high stability, and the efficiency decay rate is less than 5% after continuous operation for 500 hours.

[0119] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the perovskite light-absorbing layer and the preparation method thereof, the perovskite solar cell containing the same and the preparation method thereof, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials selected by the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A perovskite light absorbing layer, characterized in that: The perovskite light-absorbing layer is formed by combining a perovskite material and a halogen complex; The halogen complex comprises tetrakis-(4-aminophenyl)ethylene halide, wherein the benzene rings in the tetrakis-(4-aminophenyl)ethylene halide are not located in the same plane; The molecular structure of the tetrakis-(4-aminophenyl)ethylene halide is shown in the following formula I: ; Formula I The benzene rings in formula I are not located in the same plane, and the anion X - Selected from Cl - Br - or I - Any one or a combination of at least two of the following.

2. The perovskite light absorbing layer according to claim 1, characterized in that: The structure of the perovskite material is ABX3, where A is FA + 、MA + or Cs + Any one or a combination of at least two of the following: B is Pb 2+ and / or Sn 2+ ; X is Cl - Br - or I - Any one or a combination of at least two of the following.

3. The perovskite light absorbing layer according to claim 1, characterized in that: The thickness of the perovskite light-absorbing layer is 200-800 nm.

4. A method for preparing a perovskite light absorbing layer according to any one of claims 1 to 3, characterized in that: The perovskite light-absorbing layer is prepared by a solution method, and an anti-solvent is added during the film-forming process of the perovskite precursor solution.

5. The preparation method according to claim 4, characterized in that: In the perovskite precursor solution, Pb 2+ and / or Sn 2+ The concentration of is 0.5-2 mol / L, and the concentration of halogen complex is 0.5-20 mg / mL.

6. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the perovskite light-absorbing layer according to any one of claims 1 to 3.

7. The perovskite solar cell according to claim 6, characterized in that: The perovskite solar cell includes a single-junction perovskite solar cell or a stacked perovskite solar cell.

8. The perovskite solar cell according to claim 7, characterized in that: The single-junction perovskite solar cell comprises, from bottom to top, a transparent electrode, a first transmission layer, a perovskite light-absorbing layer, a second transmission layer and a metal electrode.

9. The perovskite solar cell according to claim 7, characterized in that: The stacked perovskite solar cell is formed by using a crystalline silicon cell as a substrate and connecting the single-junction perovskite solar cell in series via a tunneling layer.

10. The perovskite solar cell according to claim 8, characterized in that: The first transport layer is an electron transport layer, and the second transport layer is a hole transport layer; or, the first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.

11. A method for preparing a perovskite solar cell according to claim 8, characterized in that: The method for preparing the single-junction perovskite solar cell comprises the following steps: (1) depositing a first transport layer on the transparent electrode; (2) mixing a perovskite precursor material, a halogen complex and a solvent to obtain a perovskite precursor solution, coating the perovskite precursor solution on the first transport layer, adding an anti-solvent during the film formation process, and heating to obtain a perovskite light absorbing layer; (3) depositing a second transmission layer on the perovskite light absorbing layer, and finally evaporating a metal electrode on the second transmission layer to obtain the single-junction perovskite solar cell.

12. The preparation method according to claim 11, characterized in that: In the perovskite precursor solution of step (2), Pb 2+ and / or Sn 2+ The concentration of is 0.5-2 mol / L, and the concentration of halogen complex is 0.5-20 mg / mL.

13. A method for preparing a perovskite solar cell according to claim 9, characterized in that: The method for preparing the stacked perovskite solar cell comprises the following steps: The single-junction perovskite solar cell and the crystalline silicon cell are connected in series via a tunneling layer to obtain the stacked perovskite solar cell.